MAKANAN SATWIKA DAN PROFIL LIPID PADA BHAKTA SAI DENPASAR - Gede Ngurah Budiyasa (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2016)
Sattvik food is a social phenomenon in food consumption. Sativik food almost qual to vegetarian food. The menu is popular among the Saa Baba devotees spiritual group. Sattvik food was listed in the Bhagawad Gita XVI1.8, are foods that exalts life, energy, strength, health, happiness andjoy, a sweet, soft, contains a lot of nutrients, and tastes good is favored by wise people (sattvik). Sattvik food associated with materials, obtaining, tools used, how to cook and eat them. Before consumption must be chanted Brahmaarpanam prayer (mantram). Sattvik food can maintain lipid profile remained normal at the age of forty years above.